ANALYSIS THE EFFECT OF SERVICE QUALITY ON PATIENT SATISFACTION AT THE DENTAL CLINIC OF PUSKESMAS TANJUNGSARI BOGOR REGENCY WEST JAVA (A SURVEY OF PATIENTS DIAGNOSED WITH PULPITIS) - Astsania Hikmah Alfath; Vip Paramarta; Taufan Nugroho; Ayu Laili Rahmiyati; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
According to the 2023 Indonesian Health Survey, 50% of the population has dental and oral problems, but only 11.2% seek treatment. The Tanjungsari Community Health Center dental clinic had 1,070 pulpitis patients from January to June 2025. This study aims to analyze the effect of service quality on patient satisfaction in the dental clinic with pulpitis diagnosed at Tanjungsari Community Health Center in Bogor Regency, West Java. The research design used was quantitative method with a descriptive approach. Data were collected from 119 respondents via questionnaire and analyzed using SPSS software. The variables studied included service quality aspects of reliability, responsiveness, assurance, empathy, and tangibles. The results showed, based on a partial t-test, service quality in the aspects of reliability (p=0.02) and tangibles (p=0.00) significantly influenced patient satisfaction. A simultaneous F-test showed that service quality simultaneously influenced patient satisfaction, with a calculated F-value of 18.895. The results of this study are recommended to the Head of the Community Health Center, the Health Service, and Community Leaders to improve the quality of services at the Tanjungsari Community Health Center dental clinic by adding human resources, regular training for community health center officers, and routine monitoring and evaluation of patient satisfaction.